Real Time Monitoring of Soil Moisture for Automatic Plant Watering System - Datta, Soham; Saha, Amrita; Paul, Debabrata; Jana, Roni; Roy, Amartya (International Journal of Computer Sciences and Engineering, 2025)
Planting trees is a great thing. But sometimes it becomes quite difficult for us to supply them water in the right time so when we are outside home then to keep them alive. So to solve this kind of situation, we have developed a model which can water trees by itself from water reservoir. In this paper we have implemented soil moisture sensor which can detects the humidity level of the soil. Here we have used Arduino Uno in which ATmega328P microcontroller controls the whole system. In this paper the soil moisture sensor will detect the moisture level of a particular area and whether there is any need of water or not. Depending on the soil moisture sensor signal, the Arduino Board command the pump to water the soil still not it reaches to its desired moisture level. After that it will be de-activated again by the command of Arduino Uno. Here to control the signal of activation of the mini water pump we use D.H. Motor Driver Board. So here the construction will help people to water their garden in the case when they are outside home